2018
DOI: 10.1177/0011000018795296
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Knowledge and Attitudes Among Psychologists and Graduate Students

Abstract: Abortion is often misunderstood and steeped in misinformation. Laypeople and medical professionals tend to have limited abortion knowledge. Among the public, individuals who hold accurate information about abortion are more likely to endorse pro-choice attitudes than individuals who are misinformed. We explored knowledge of, and attitudes toward, abortion among 142 psychologists and graduate students. Participants responded accurately, on average, to 68% of the items on a true-false measure of abortion knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…It is revealed that young people with higher education, who have accurate information about abortion, support the position in favor of abortion more often than those who are misinformed [14]. The results of studies indicate a high level of sexual activity of student youth, as well as a low level of contraceptive use and a negative attitude towards modern methods of contraception.…”
Section: Figure 2 the Views Of The Respondents On The Gender Of A Firstbornmentioning
confidence: 99%
“…It is revealed that young people with higher education, who have accurate information about abortion, support the position in favor of abortion more often than those who are misinformed [14]. The results of studies indicate a high level of sexual activity of student youth, as well as a low level of contraceptive use and a negative attitude towards modern methods of contraception.…”
Section: Figure 2 the Views Of The Respondents On The Gender Of A Firstbornmentioning
confidence: 99%
“…Given the lack of quality sex education in schools and in families (Flores & Barroso, 2017), U.S. American adults’ knowledge about sex is generally inadequate, with limited understanding about pregnancy risks and types and effectiveness of contraception (Cabral et al, 2018), trouble distinguishing between emergency contraception and medication abortion (Hickey, 2009), and underestimating the risks of giving birth while overestimating the risks of using contraception (Wiebe et al, 2015). These insufficient levels of sexual health knowledge extend to health care practitioners including medical students (Warner et al, 2018) and psychologists and psychology graduate students (Mollen, Hargons, et al, 2018). The state of sex education in the U.S. impacts clients’ sexual knowledge whom health service psychology trainees serve and likewise influences trainees’ sexual knowledge, especially those educated in the U.S. Sexuality education is necessary for psychologists to be adequately prepared to provide competent care to those with whom they will work.…”
Section: Sex Education In the United Statesmentioning
confidence: 99%
“…Among clinical and counseling psychology training programs in the U.S. and Canada, human sexuality courses are rarely offered and when available, are typically electives (Asher, 2007; Wiederman & Sansone, 1999). Though graduate programs typically provide training related to LGBTQ identities and sexual abuse and trauma, very few attend to diverse sexual expression, reproduction, sexual ethics, and sexual health (Mollen, Hargons, et al, 2018). Relatedly, psychologist trainees report discomfort discussing sexuality (Hanzlik & Gaubatz, 2012).…”
Section: Sex Education In the United Statesmentioning
confidence: 99%
“…Values related to abortion may be strongly tied to knowledge about abortion, as studies have shown that individuals with more accurate abortion information feel more favorably about abortion (Mollen et al, 2018). Thus, misinformation about abortion (e.g., the false idea that abortion is dangerous or causes health problems; Rowlands, 2011) may cause a person to feel fear or opposition to abortion (White et al, 2016).…”
Section: The Proposed Pdmmmentioning
confidence: 99%
“…But the process of pregnancy decision-making and the consideration of psychological factors that may influence pregnancy decisions have rarely been explored. Given recent calls for psychologists to contribute to reproductive justice research (Grzanka & Frantell, 2017; Mollen et al, 2018), we aim to improve public understanding of the psychological process of pregnancy decision-making in the context of unintended pregnancy.…”
mentioning
confidence: 99%